Сучасний стан та тенденції розвитку житлово-комунального господарства України - Шахова, О. В. (НТУ "ХПІ", 2014)
Визначені основні проблеми житлово-комунального господарства України. Наведені основні параметри розвитку інфраструктури житлово-комунального господарства. Доведено, що розвиток житлово-комунального господарства є складним завданням і вимагає раціонального поєднання централізованого планово-збалансованого керівництва із спеціалізацією його найважливіших функцій в розрізі галузей і підгалузей, уніфікації їх за видами виробничої діяльності. Визначено, що пріоритетним напрямком подальших ринкових трансформацій ЖКГ має стати формування сприятливого інвестиційного клімату в галузі.

The main problems of housing and communal services of Ukraine. Areas in need of attention and control by the state, regional authorities and managers of housing and communal services. The basic parameters of infrastructure development of housing and communal services. It is proved that the development of housing and communal services is a challenging task and requires a rational combination of centralized planning and balanced management with specialization of its most important functions across sectors and sub-sectors, unifying their production by type of activity. Determined that the priority of further market transformations utilities should be the formation of a favorable investment climate in the industry. This approach will help stabilize the financial condition of the utilities in the long term, provided that the investment projects will focus on intensive capacity building, introduction of new technologies and engineering services.
Current status and trends of development of housing and communal services of Ukraine
Keywords: житлово-комунальне господарство; ЖКГ; інфраструктура ЖКГ; проблеми галузі ЖКГ; housing and communal services; development